Eerdmans handbook to the Bible - Alexander, David, 1937-; Alexander, Pat, 1937- (Grand Rapids, Mich. : Eerdmans, 1973)
A section-by-section guide to the Bible. Includes pictures, articles, maps, charts, and an index of people, places, events, and themes.
Keywords: Bible. -- Handbooks, manuals, etc; Bible. -- Guides, manuels, etc